Future prevention and handling of environmental accidents - Bertazzi, Pier A. (Scandinavian Journal of Work, Environment & Health, 1999)
According to the 1995 World Disaster Report, accidents are second only to floods in frequency. Chemical accidents leading to a serious danger to the general public and to the environment rank 10th, just after epidemics and followed by landslides. Can the occurrence of these environmental accidents be reduced in the future and their consequences minimized? The answer is yes, provided that decisions are made and actions implemented now. Future management of environmental accidents requires that the same effort so far devoted to relief measures in the postimpact phase be devoted to advance planning in the preaccident period. International cooperation should be activated to predispose risk reduction measures, including a hazard-oriented approach to prevention, preparedness plans for possible incidents in major hazardous installations, and collaborative programs and resource sharing for response to accidents and the follow-up of their consequences. Clear and unequivocal communication with the public, with other professionals, decision makers, and the media play a key role in each step.
Keywords: accident prevention; disaster preparedness; emergency response; environmental health; industrial accident